Revisiting Hedonism in QS. Al-Hadid Verse 20: Integrating Tafsir ‎and Neuroscience on Reward, Self-Control, and Spiritual Awareness - Sukriati Sukriati; Muhammad Kudhori (Jurnal Ulunnuha, 2025)
This study departs from the question of how the mechanism of self-regulation failure in hedonistic behavior can be explained through the integration of the spiritual message of QS. Al-Hadīd verse 20 and the neurobiological functions of the brain. The aim is to dissect the roots of the hedonistic lifestyle and synchronize brain function with spiritual awareness in dealing with attachment to instant gratification. Using a descriptive-analytical qualitative method with normative-empirical integration techniques, this study connects classical and contemporary interpretive data with neuroscience findings. The research findings show that the stages of worldly pleasures in the verse (la'ib, lahw, zīnah, tafākhur, takāthur) correlate directly with a surge of dopamine in the brain's addictive and deceptive reward system, which can physically weaken the function of the prefrontal cortex as the center of executive function. The theoretical contribution of this research lies in strengthening the exegesis literature through empirical neuroscience evidence and repositioning the concept of mujahadatun nafs not merely as a moral doctrine, but as a process of strengthening the brain's cognitive functions to moderate human biological impulses.